Penyusunan Aspek Digital Village Index Desa Damai Kabupaten Maros dengan Metode Design Science - Siskanti Siskanti; Eliyah A M Sampetoding; Muhammad Hasbi (Compromise Journal Community Proffesional Service Journal, 2024)
Advances in Information and Communication Technology (ICT) have changed the paradigm in various sectors of life, including education, health services, government and the economy. In the ever-evolving digital era, digitalization has become a significant global trend, influencing the way we communicate and interact, including in villages. Villages, as legal community entities with unique characteristics, are the center of attention in digital transformation in Indonesia. However, to measure the level of success of digitalization in villages, an index is needed that can provide an objective picture. In this context, the Digital Village Index (DVI) exists as an evaluation tool that allows the government and stakeholders to identify areas that require improvement and plan more effective development strategies. The Damai Village case study uses a Design Science approach to develop a comprehensive and relevant DVI, with the hope of formulating appropriate strategies to accelerate the digitalization process in the village, according to local characteristics and needs.